KONFLIK KERJA DAN MODAL: KONSTRIBUSI PERSONALISME DALAM ENSIKLIK LABOREM EXERCENS - Petrus Canisius Edi Laksito (Lembaga Penelitian STKIP Widya Yuwana, 2022)
This article wants to discuss the social teaching of Pope John Paul II regarding the conflict between work and capital in his encyclical Laborem Exercens. Karl Marx (1818-1883) holds that in an capitalistic industrial world, work is represented by the worker class as work force, while capital is represented by the entrepeneurs, owners or holders of the means of production. In Laborem Exercens art. 11-15, the Pope mentions this issue of the relationship of work and capital from the perspective of Christian personalism, proposing the principle of the priority of work over capital as the basis for regulating work in general and industry in particular. From this study, it is hoped that several consequences can be drawn for studies and efforts about work that are based on a personalistic vision of man